Phytoplankton Community Performance Depends on the Frequency of Temperature Fluctuations - Kunze, Charlotte; Gerhard, Miriam; Jacob, Marrit; Franke, Niklas Alexander; Schröder, Matthias; Striebel, Maren (Frontiers in Marine Science, 2022)
With increasing frequency and intensity of climate change events, it is crucial to understand how different components of temperature fluctuations affect the thermal tolerance and performance of marine primary producers. We used a controlled indoor-mesocosm set-up to test the effect of a temperature fluctuation frequency gradient on a natural phytoplankton community. Within a frequency gradient, we allowed the temperature to fluctuate from 18 ± 3°C at different rates (6, 12, 24, 36, and 48 h). The temperature fluctuation frequency gradient was contrasted to a constant temperature treatment with the same mean temperature (18°C). Phytoplankton biomass tended to increase with faster fluctuations but was lowest in the diurnal frequency treatment (24 h). In comparison with constant conditions, diurnal or slower fluctuation frequencies showed lower or comparable performance, whereas faster fluctuations showed higher performance. In addition, minor differences in community structure were observed, but species diversity remained comparable over time. Similarly, resource use efficiency and stoichiometry did not change according to fluctuation frequency treatments. We conclude that the effect of temperature fluctuations on phytoplankton biomass depends on the fluctuation frequency; this suggests that the fluctuation frequency determines how organisms average their environments. However, this trend is not driven by species identity but physiological responses. Our results also indicate that phytoplankton communities may be already well adapted to fluctuating environments and can adjust physiologically to temperature variability.